The Influence of Personal Branding in the Establishment of Social Media Influencer Credibility and the Effect on Brand Awareness and Purchase Intention - Luwie Luwie; Lamhot Henry Pasaribu (Institute of Computer Science (IOCS), 2021)
The purpose of this study is to analyze the phenomenon of Personal Branding, on the credibility built by social media influencers in the formation of Brand Awareness and Purchase Intention. This study uses a quantitative approach that uses the figure of Kiki Siantar as the research case and the followers of Kiki Siantar as research respondents. The method used in this research is purposive sampling with non-probability sampling and snowball sampling. The results of this study found that there is a positive and significant influence between Personal Branding in the formation of Influencer Credibility. In addition, it was also found that the credibility built by a social media influencer has a positive and significant influence in building Brand Awareness and Purchase Intention on Hellolilo products in the minds of Kiki Siantar's followers. And also found that Brand Awareness has a higher influence on purchasing decisions than Influencer Credibility.